Kaepernick Can Kick It!: Employment Discrimination, Political Activism, and Speech in the NFL - Brittney Watkins (Washington University Journal of Law & Policy, 2019)
This note addresses employment law implications of professional quarterback Colin Kaepernick’s inability to find work after engaging in public protests against police brutality. The note begins with a review of Kaepernick’s 2016 protests and subsequent difficulties securing employment with an NFL team. The note then examines relevant principles of federal antidiscrimination law, as well as New York antidiscrimination law, which might apply in Kaepernick’s situation. Both provide protection against racial discrimination, while only New York provides protection from discrimination on the basis of a narrow class of political activities. The note finds that few, if any, of these provisions would benefit Kaepernick based on their usual applications. The note proposes several solutions, including that courts should be more receptive to claims that some, but not all, members of a given racial group are facing discrimination, and that statutory protections against political discrimination should be strengthened.
Keywords: employment law; employment discrimination; Kaepernick; protest; antidiscrimination; racial discrimination